Narrative of the proceedings of pedrarias davila in the provinces of tierra firme, or castilla del oro : and of the discovery of the south sea and the coasts of peru and nicaragua - Andagoya, Pascual de (NewYork : Cambridge university press, 2009)
The publications of the Hakluyt Society (founded in 1846) made available edited (and sometimes translated) early accounts of exploration. The first series, which ran from 1847 to 1899, consists of 100 books containing published or previously unpublished works by authors from Christopher Columbus to Sir Francis Drake, and covering voyages to the New World, to China and Japan, to Russia and to Africa and India. This book, published in 1865, contains an early account of Spanish exploration on and around the Isthmus of Panama. The author accompanied Pedrarias Davila when he was appointed governor of the isthmus in 1514, and his report about the legendary riches of the Inca empire of Peru led to Pizarro's expedition and the destruction of the Inca civilisation. The translator's introductory essay describes the expedition of Balboa, who preceded Davila as governor of the isthmus, and was the first European to see the Pacific Ocean.
Includes bibliographical references and index.
Keywords: America Discovery and exploration Spanish; Panama History